The effects of dynamic vulcanization and compatibilizer on properties of paper sludge-filled polypropylene/ethylene propylene diene terpolymer composites - Salmah Husinsyah; Ismail, Hanafi A.; Azuraliza, Abu Bakar (Wiley Periodicals, 2009)
Link to publisher's homepage at http://www3.interscience.wiley.com